Railway safety by designing the layout of inland terminals with dangerous goods connected with the rail transport system. (December 2018) - Santarremigia, Francisco Enrique; Molero, Gemma Dolores; Poveda-Reyes, Sara; Aguilar-Herrando, José
Highlights: Design of inland terminals for containers with dangerous goods (ITDGs). A railway system with higher social benefits (lower risks and lower GHG emissions). Decreasing safety, security and environmental risks associated with rail ITDGs. Decision-making tool for safe, secure, green and cost-efficient rail ITDGs. Abstract: While rail transport is growing for medium-distance journeys, the first and last miles are travelled by road, marking a change of transport mode in inland terminals (ITs). Moreover, the introduction of ITs in seaport hinterlands is increasing with a view to decongesting ports, and the best transport mode to connect these ITs with ports is that of rail. In 2013, chemicals were involved in 48 rail accidents in the EU-28 and in 667 in the United States (US). An appropriate design for the layout of inland terminals for containers with dangerous goods (ITDGs) involved in the rail system will increase the safety and operability of rail transport, avoiding accidents such as Tianjin (2015). The novelty of this work is a methodology to design the layout of ITDGs involved in rail transport through a hierarchy of container handling equipment (CHE), used in the yard of the terminal for a safer, more resilient and more environmentally friendly rail transport. The AHP (analytic hierarchy process) was used to hierarchize five alternative layouts, one for each CHE used in the yard; and according to criteria belonging to three areas: safety and security, environment and equipment performance. Results show that a layout linked to platforms is the preferred alternative for storing containers with dangerous goods (DGs) in ITs connected to railways. The implementation of this methodology will reduce consequences in the case of a serious accident in, or terrorist attack on, ITDGs involved in the rail system and GHG (greenhouse gas) emissions in the terminal.